Pengaruh Pembelajaran Online Berbasis Google Classroom terhadap Hasil Belajar Siswa - Muhammad Reza Andhika; Mutia Marlianti; Ratih Purwaningrum; Puji Astuti (Teknik Informatika Universitas Pamulang, 2021)
This exploration was conducted to determine the effect of online learning using google classroom on student learning outcomes. This research was conducted with 2, 3, and 4 graders using Google Classroom. The tool used in this research is a questionnaire. Analysis of the data used is descriptive analysis and hypothesis testing using the F-test with the help of SPSS software. The F test results show that Google Classroom and online learning also affect student learning outcomes. This is obtained after seeing the value of Sig. 0.000 < 0.05. R-square test was also conducted to understand the extent to which Google Classroom and online learning affect student learning outcomes. According to the results of the R-square test, Google Classroom and online learning were found to have an effect of 53.8% on student learning outcomes.